Peptida Polisakarida: Anti Inflamasi dan Anti Oksidan yang Menjanjikan pada Atherosklerosis - Indra Prasetya; Ria Ashriyah; Ira Setyawati; Joko Hermawan; Widyo Mahargo; Yunita Leksono; Titin Andri W.; Teuku Heriansyah; Muhammad Aris W.; Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2015)
Background : Heart disease is the leading cause of death for both men and women, but heart disease is preventable and controllable. Ganoderma lucidum is widely used as traditional medicine for centuries particularly in China, Japan, and Korea. Previous study showed antioxidative activity of polysaccharide peptide (PsP) from Genoderma lucidum.Objective : This study was aimed to evaluate anti-inflammatory and antioxidant effect of polysaccharide peptide (PsP) from Ganoderma lucidum in atherosclerotic rats.Methods : The atherosclerotic rats were randomly divided into four groups (5 rats each group) : atherosclerotic model with high-fat diet, low dose PsP treated group (50 mg/kgBW), medium dose PsP treated group (150 mg/kgBW), high dose PsP treated group (300 mg/kgBW), with normal mice used as a control group. Parameters measured were the level of MDA, SOD, IL - 6 , IL - 10, hsCRP, TNF - ?, lipid profile and foam cell.Results : After PsP therapy for 5 weeks, the levels of MDA (p=0.01), hsCRP (p=0.018) in rats model of atherosclerosis decrease significantly. PsSP can reduce levels of IL - 6 (p=0.933) and increase levels of SOD (p=0.28) descriptively at PsP doses 150 mg/kgBW. While the levels of TNF-? (p=0.894) and IL-10 (p=0.98) was not affected by administration of PsP. PsP improve the lipid profile by increasing HDL (p=0.002) and lowering total cholesterol (p=0.04). The formation of foam cells (p=0.024) as a marker of atherogenesis significantly decreased by administration of PsP .Conclusion : PSP can be useful to reduce inflammatory processes and oxidative stress to prevent the process of atherogenesis.